On the distribution of the marine genus Thinolestris Grootaert & Meuffels (Diptera, Dolichopodidae) with a description of a new species from Singapore, Malaysia and Brunei - Grootaert, Patrick; Evenhuis, Neal L. (Zootaxa, 2006)
Four species of Thinolestris Grootaert & Meuffels are known so far, including T. nigra sp. nov., which is described here from Singapore, Malaysia and Brunei. New morphological data on the genus are given. At the moment, Thinolestris is only known from Andaman Sea, Strait of Singapore, South China Sea, Celebes Sea, Bismarck Sea and the Coral Sea. It is not yet known from North Australia nor from the Gulf of Thailand, or farther north. Thinolestris adults are active on beaches with small pebbles mixed with sandy patches. It is not found on rocks, pure sandy beaches nor mangroves.